2020
DOI: 10.1108/gkmc-06-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

A trustworthy network or a technologically disguised scam

Abstract: Purpose The initiation of cryptocurrency such as bitcoin has invoked a general curiosity in the international financial regime. Bitcoin works in a peer-to-peer framework with no third party acting as a monitoring agency. This brings in both positive and negative spirit to the table. Though generic understanding is available, the studies done on bitcoin and blockchain are far and few. The purpose of this paper is to decipher the level of understanding the scientific world has on bitcoin and the underlying block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Within organizations, knowledge hiding is generally observed in different forms such as playing dumb, evasive hiding, rationalized hiding, and counter-questioning (Connelly et al ., 2012; Jha and Varkkey, 2018). Academic researchers have established the existence of multiple strategic factors that engender knowledge hiding, including job insecurity (Ashford et al ., 1989; De Witte, 1999; Serenko and Bontis, 2016), workplace ostracism (Bogilović et al ., 2017; Černe et al ., 2017), territoriality (Peng, 2013; Singh, 2019), trust deficit (Ford and Staples, 2010; Issac and Baral, 2020a), complexity and uncertainty of task (Boz Semerci, 2019; Hernaus et al ., 2019; Kang, 2016), reciprocity (Ayub et al ., 2021; Zhao et al ., 2016), personality traits (Demirkasimoglu, 2015; Jain and Jain, 2014), emotional intelligence (Burmeister et al ., 2019; de Geofroy and Evans, 2017), and the non-availability of knowledge management systems (Issac and Baral, 2020b; Lanke, 2018). Research has also shown that knowledge hiding could be mitigated to a certain extent with the aid of ethical leadership (Koay and Lim, 2022), keeping a check on organizational politics (Al-Alawi et al ., 2007; Qureshi and Evans, 2015), avoiding externalities such as time pressures (Škerlavaj et al ., 2018) and dynamic cultural strength coupled with pro-social motivation (Demirkasimoglu, 2015; Issac et al ., 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Within organizations, knowledge hiding is generally observed in different forms such as playing dumb, evasive hiding, rationalized hiding, and counter-questioning (Connelly et al ., 2012; Jha and Varkkey, 2018). Academic researchers have established the existence of multiple strategic factors that engender knowledge hiding, including job insecurity (Ashford et al ., 1989; De Witte, 1999; Serenko and Bontis, 2016), workplace ostracism (Bogilović et al ., 2017; Černe et al ., 2017), territoriality (Peng, 2013; Singh, 2019), trust deficit (Ford and Staples, 2010; Issac and Baral, 2020a), complexity and uncertainty of task (Boz Semerci, 2019; Hernaus et al ., 2019; Kang, 2016), reciprocity (Ayub et al ., 2021; Zhao et al ., 2016), personality traits (Demirkasimoglu, 2015; Jain and Jain, 2014), emotional intelligence (Burmeister et al ., 2019; de Geofroy and Evans, 2017), and the non-availability of knowledge management systems (Issac and Baral, 2020b; Lanke, 2018). Research has also shown that knowledge hiding could be mitigated to a certain extent with the aid of ethical leadership (Koay and Lim, 2022), keeping a check on organizational politics (Al-Alawi et al ., 2007; Qureshi and Evans, 2015), avoiding externalities such as time pressures (Škerlavaj et al ., 2018) and dynamic cultural strength coupled with pro-social motivation (Demirkasimoglu, 2015; Issac et al ., 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study essentially identifies the same as an important external factor in engendering knowledge hiding and finally find its place in the conceptual framework. The characteristics of the job or task motivate the knowledge seeker and the hider to play their relevant roles during any dyadic exchange (Issac & Baral, 2020). The organizational environment is equally critical in facilitating knowledge sharing or making individuals disengaged from knowledge hiding (Issac & Thomas, 2019; Mowbray, Wilkinson, & Tse, 2015; Thomas & Issac, 2018; Vasconcelos, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is the first cryptographic commodity that can be traded like cash. It has risen to become the world's most popular cryptocurrency in recent years, with an increasing number of businesses accepting it as payment, fostering a crypto‐driven society (Issac & Baral, 2020; Ostapowicz & Żbikowski, 2020).…”
Section: Introductionmentioning
confidence: 99%